The Effect of Thiamine and Thiamine Pyrophosphate on Oxidative Liver Damage Induced in Rats with Cisplatin. (6th June 2013) - Turan, Mehmet Ibrahim; Siltelioglu Turan, Isil; Mammadov, Renad; Altınkaynak, Konca; Kisaoglu, Abdullah
Abstract : The aim of this study was to investigate the effect of thiamine and thiamine pyrophosphate (TPP) on oxidative stress induced with cisplatin in liver tissue. Rats were divided into four groups; thiamine group (TG), TPP + cisplatin group (TPG), healthy animal group (HG), and cisplatin only group (CG). Oxidant and antioxidant parameters in liver tissue and AST, ALT, and LDH levels in rat sera were measured in all groups. Malondialdehyde levels in the CG, TG, TPG, and HG groups were 11 ± 1.4, 9 ± 0.5, 3 ± 0.5, and 2.2 ± 0.48  μ mol/g protein, respectively. Total glutathione levels were 2 ± 0.7, 2.8 ± 0.4, 7 ± 0.8, and 9 ± 0.6 nmol/g protein, respectively. Levels of 8-OH/Gua, a product of DNA damage, were 2.7 ± 0.4 pmol/L, 2.5 ± 0.5, 1.1 ± 0.3, and 0.9 ± 0.3 pmol/L, respectively. A statistically significant difference was determined in oxidant/antioxidant parameters and AST, ALT, and LDH levels between the TPG and CG groups (P < 0.05 ). No significant difference was determined between the TG and CG groups (P > 0.05 ). In conclusion, cisplatin causes oxidative damage in liver tissue. TPP seems to have a preventive effect on oxidative stress in the liver caused by cisplatin.